Pylephlebitis complicating acute diverticulitis - Azorín Samper, María del Carmen; Ruiz Carmona, María Dolores; Checa Ayet, Félix (Cirugía del Uruguay, 2020)
A 60-year-old man with a history of appendectomy and diverticulosis of the colon. He went to the Emergency Department for a general malaise, fever, nausea and vomiting of two days of evolution. On examination, a soft and depressible, painful abdomen in the left iliac fossa.